2020
DOI: 10.1007/s40279-020-01299-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Technical Skills in Talented Youth Athletes: A Systematic Review

Abstract: Background Talent identification and development (TID) programs aim to identify players with the greatest potential for long-term success. Previous research suggests that the assessment of sport-specific technical skills is valuable for discriminating between more and less skilled individuals and/or for predicting future performance. Objective This review aims to provide an overview on both the instruments used to assess sport-specific technical skills and their discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 105 publications
2
49
0
Order By: Relevance
“…Second, within this study, the proper passing options were determined a priori based on the expert evaluation. However, the successful execution of a made decision depends on a player’s technical skills [ 8 ] and is also influenced by contextual factors (e.g., the status of time or score) [ 66 ] which is usually not represented within laboratory settings. Third, a common limitation of video-based assessments without a specific response is the lack of perception-action-coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, within this study, the proper passing options were determined a priori based on the expert evaluation. However, the successful execution of a made decision depends on a player’s technical skills [ 8 ] and is also influenced by contextual factors (e.g., the status of time or score) [ 66 ] which is usually not represented within laboratory settings. Third, a common limitation of video-based assessments without a specific response is the lack of perception-action-coupling.…”
Section: Discussionmentioning
confidence: 99%
“…In general, sports performance is moderated by multiple interdependent variables including physiological, biomechanical, and psychological factors [ 5 ]. In the past years, extended research concerning physical factors was conducted [ 6 ] while the role of other performance factors such as psychological factors attracted less attention [ 7 , 8 ]. To specify, these factors incorporate psychomotor, cognitive, and personality-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the reviews for sport (Sarmento et al, 2018;Koopmann et al, 2020) or soccer skills (Murr et al, 2018a;Williams et al, 2020), the present study underlines the importance of technical skills. The median effect size for dribbling (d = 0.47) in this study was at the lower end of the range of effect sizes that Murr et al (2018a) identified in 10 prospective soccer studies (0.47 ≤ d ≤ 1.24).…”
Section: Technical Skills (Motor Domain)mentioning
confidence: 69%
“…A further limitation is that this study only investigated male players. With a few exceptions (Datson et al, 2020;Leyhr et al, 2020b), this is typical of talent research in sport, with an overrepresentation of male studies in general (Johnston et al, 2018;Koopmann et al, 2020) and in soccer (Murr et al, 2018b;Sarmento et al, 2018). However, gender must be considered as a potential moderator variable regarding the prognostic relevance of talent predictors, and thus, future studies should extend their focus to female athletes (Williams et al, 2020), in particular due to the increasing popularity of female soccer (Manson et al, 2014).…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…These studies emphasize the predictive value of technical characteristics for future sports performance. A recent systematic review also demonstrated the great capability of sport-specific technical characteristics assessments to predict future performance [ 30 ]. Especially in an early-entry sport as tennis, sport-specific technical characteristics seem to be crucial for future performance given the specific competences to be developed from an early age.…”
Section: Discussionmentioning
confidence: 99%